Low rates of X‐Y recombination, not turnovers, account for homomorphic sex chromosomes in several diploid species of Palearctic green toads (Bufo viridis subgroup). (14th January 2013) - Stöck, M.; Savary, R.; Betto‐Colliard, C.; Biollay, S.; Jourdan‐Pineau, H.; Perrin, N.
Abstract Contrasting with birds and mammals, most ectothermic vertebrates present homomorphic sex chromosomes, which might be due either to a high turnover rate or to occasional X‐Y recombination. We tested these two hypotheses in a group of Palearctic green toads that diverged some 3.3 million years ago. Using sibship analyses of sex‐linked markers, we show that all four species investigated share the same pair of sex chromosomes and a pattern of male heterogamety with drastically reduced X‐Y recombination in males. Phylogenetic analyses of sex‐linked sequences show that X and Y alleles cluster by species, not by gametolog. We conclude that X‐Y homomorphy and fine‐scale sequence similarity in these species do not stem from recent sex‐chromosome turnovers, but from occasional X‐Y recombination.